When the Utopian Performative Encounters Beauty - Skjoldager-Nielsen, Daria (Nordic Theatre Studies, 2023)
I remember the first time I came across the utopian performative: the butterflies in my stomach, the overwhelming feeling of hope and happiness it produced. Jill Dolan [2005] points to those moments during performances when the audience comes together and feels hopeful; moments that constitute inspiration for change: for the performer, the spectator, and maybe even the world – and which are often (understandably) politically or socially charged. But my experiences were different: my feeling of hope was not emerging after watching a political vision of the future, but during and after my encounters with beauty. I began to wonder: can a profound sense of beauty that brings the feeling of hope and love, also have the potential to change the world? In this article, I explore the aesthetics of the theatrical event and its effectiveness in bringing out utopian performatives. Theoretically, I draw on Erika Fischer-Lichte’s aesthetics of the performative to show how the language of performance analysis can access a theatrical (aesthetic) experience and on the theory of affect in performance to understand my experience; also, I supplement Dolan’s theory with Dorthe Jørgensen’s experience of beauty to extend her thinking into non-political experiences and grasping them more fully. As an example, I discuss Oratorium Dance Project (Lodz 2011).